1966
DOI: 10.3181/00379727-122-31283
|View full text |Cite
|
Sign up to set email alerts
|

An Anomalous Effect of Theophylline on ACTH and Adenosine 3',5'-Monophosphate Stimulation.

Abstract: every 2 months to a maximum of 100 mg/day. He noted clinical improvement with 1 5 mg, but said it was less rapid than that with 50 and 100 mg/day. However, the clinical picture is not generally considered to be consistent enough to allow such fine discrimination in drug response, and in most clinical trials it has been found necessary to assess the drug by the bacteriologic response in groups of lepromatous cases, each group on a particular dosage for a year or more.Thus it seems indicated to test the therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1967
1967
1979
1979

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…1). This agrees qualitatively with the previous findings of Halkerston et al (1966), who demonstrated that 1 mM theophylline enhanced ACTH stimulation of adrenal steroidogenesis by protection of the cAMP formed intracellularly, and that 10mM theophylline inhibited it by means of partial inhibition of protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…1). This agrees qualitatively with the previous findings of Halkerston et al (1966), who demonstrated that 1 mM theophylline enhanced ACTH stimulation of adrenal steroidogenesis by protection of the cAMP formed intracellularly, and that 10mM theophylline inhibited it by means of partial inhibition of protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, some discrepancies exist. Halkerston et al (1966) reported theophylline (10 mM) to have two antagonistic adrenal actions, a small potentiation of ACTH simulated steroidogenesis, and inhibition of such in addition to inhibition of protein synthesis. Further, theophylline (Bieck et al 1969) and caffeine (Kitabchi et al 1971) have antagonistic effects upon ACTH and cAMP stimulated steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the substances listed in the preceding paper [l 1, neurotensin, substance P, Leu-enkephalin and Leu" human gastrin I (with leucine at residue 15) were purchased from Beckman and synthetic somatostatin from Serono. Synthetic octapeptide of cholecystokinin was generously supplied by M. Ondetti (Squibb) and bovine pancreatic peptide by R. E. Chance (Lilly).…”
Section: Methodsmentioning
confidence: 99%
“…lowering the magnitude of the vasoactive intestinal peptide stimulation. Furthermore, high concentrations of methylxanthine derivatives are known to induce undesirable side effects on other enzyme activities [14] or on protein synthesis [15].…”
Section: Effect Of Time Temperature Phosphodiesterase Inhibitor Andmentioning
confidence: 99%